Core Java. Volume I. Fundamentals - Horstmann, Cay S. (USA : Pearson Education, 2022)
Core Java, Volume I: Fundamentals, Twelfth Edition, is the definitive guide to writing robust, maintainable code. Whatever version of Java you are using---up to and including Java 17---this book will help you achieve a deep and practical understanding of the language and APIs. With hundreds of realistic examples, Cay S. Horstmann reveals the most powerful and effective ways to get the job done. This book is written for readers with prior programming experience who are looking for in-depth coverage of the Java language and platform. You'll learn about all language features in detail, including the recent improvements in Java 17. The applied chapters and code examples cover the most up-to-date capabilities of the vast Java library. For 25 years, Core Java has prepared serious programmers for serious Java programming.
Keywords: Computer; Core; Fundamentals; Java